New records and new species of gall midges (Diptera: Cecidomyiidae) developing on Chenopodiaceae in Egypt - Elsayed, Ayman Khamis; Skuhravá, Marcela; Karam, Hedaya Hamza; Elminshawy, Abdelaziz; Al-Eryan, Mohamed Awad (Zootaxa, 2015)
The Cecidomyiidae (Diptera: Bibionomorpha) fauna of Egypt is poorly known. Investigations in northern Egypt in 2013 revealed the presence of seven species of gall midges on three host plant species: Atriplex halimus L., Arthrocnemum macrostachyum (Moric.) and Suaeda pruniosa Lange (all Chenopodiaceae). Among the gall midges, Baldratia salicorniae Kieffer and Stefaniella trinacriae De Stefani are reconfirmed records in Egypt; Houardiella gracilis Dorchin & Freidberg and Asphondylia punica Marchal are new records; and Baldratia karamae Elsayed & Skuhraván. sp. , Primofavilla aegyptiaca Elsayed n. sp. and Stefaniella skuhravae Elsayed n. sp. are new to science. Adult morphology of the latter three new species is described and illustrated, and their biology and geographic distribution are given.